Democracy and fake news : information manipulation and post-truth politics - Giusti, Serena editor.; Piras, Elisa editor. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores the challenges that disinformation, fake news and post-truth politics pose to democracy from a multidisciplinary perspective. The authors analyse and interpret how the use of technology and social media as well as the emergence of new political narratives has been progressively changing the information landscape, undermining some of the pillars of democracy. The volume sheds light on some topical questions connected to fake news, thereby contributing to a fuller understanding of its impact on democracy. In the Introduction, the editors offer some orientating definitions of post-truth politics, building a theoretical framework where various different aspects of fake news can be understood. The book is then divided into three parts: Part I helps to contextualise the phenomena investigated, offering definitions and discussing key concepts as well as aspects linked to the manipulation of information systems, especially considering its reverberation on democracy. Part II considers the phenomena of disinformation, fake news and post-truth politics in the context of Russia, which emerges as a laboratory where the phases of creation and diffusion of fake news can be broken down and analysed; consequently, Part II also reflects on the ways to counteract disinformation and fake news. Part III moves from case studies in Western and Central Europe to reflect on the methodological difficulty of investigating disinformation, as well as tackling the very delicate question of detection, combat and prevention of fake news. This book will be of great interest to students and scholars of political science, law, political philosophy, journalism, media studies, and computer science, since it provides a multidisciplinary approach to the analysis of post-truth politics"-- Includes bibliographical references and index. Introduction : in search of paradigms : disinformation, fake news, and post-truth politics / Serena Giusti and Elisa Piras -- Reading Arendt to rethink truth, science and politics in the era of fake news / Federica Merenda -- Inequality in the public sphere : epistemic injustice, discrimination and violence / Elisa Piras -- Incorporating intersectionality into AI ethics / Liza Ireni-Saban and Maya Sherman -- How post-truth politics transformed and shaped the outcome of the 2016 Brexit referendum / Jennifer Cassidy -- Information and democracy : fake news as an emotional weapon / Matthew Loveless -- Searching for a unicorn : fake news and electoral behaviour / Luigi Curini and Eugenio Pizzimenti -- Once upon Covid-19 : a tale of misleading information going viral / Alice Hazelton -- Lie to live : the production of a faked reality as an existential function of Putin's regime / Anna Zafesova -- Playing the Russian disinformation game : information operations from Soviet tactics to Putin's sharp power / Francesco Bechis -- Myths and realities of Putinism in post-truth politics / Mara Morini -- Responding to alleged Russian interference by focusing on the vulnerabilities that make it possible / Giorgio Comai -- Information spreading and the role of automated accounts on Twitter : two case studies / Guido Caldarelli, Rocco De Nicola, Marinella Petrocchi, and Fabio Saracco -- Radical-right political activism on the Web and the challenge for European democracy : a perspective from Eastern and Central Europe / Manuela Caiani and Pál Susánszky -- When a credible source turns 'fake' : the Relotius affair and the German system for combatting fake news / Mihail Stojanoski -- "But verifying facts is what we do!" : fact-checking and journalistic professional autonomy / Urban Larssen -- The EU Code of Practice on Disinformation and the risk of the privatisation of censorship / Matteo Monti. "This book explores the challenges that disinformation, fake news and post-truth politics pose to democracy from a multidisciplinary perspective. The authors analyse and interpret how the use of technology and social media as well as the emergence of new political narratives has been progressively changing the information landscape, undermining some of the pillars of democracy. The volume sheds light on some topical questions connected to fake news, thereby contributing to a fuller understanding of its impact on democracy. In the Introduction, the editors offer some orientating definitions of post-truth politics, building a theoretical framework where various different aspects of fake news can be understood. The book is then divided into three parts: Part I helps to contextualise the phenomena investigated, offering definitions and discussing key concepts as well as aspects linked to the manipulation of information systems, especially considering its reverberation on democracy. Part II considers the phenomena of disinformation, fake news and post-truth politics in the context of Russia, which emerges as a laboratory where the phases of creation and diffusion of fake news can be broken down and analysed; consequently, Part II also reflects on the ways to counteract disinformation and fake news. Part III moves from case studies in Western and Central Europe to reflect on the methodological difficulty of investigating disinformation, as well as tackling the very delicate question of detection, combat and prevention of fake news. This book will be of great interest to students and scholars of political science, law, political philosophy, journalism, media studies, and computer science, since it provides a multidisciplinary approach to the analysis of post-truth politics"--